RELATIVE PERFORMANCE OF F1 AND F2 INTRAHIRSUTUM HYBRIDS FOR SOME QUANTITATIVE TRAITS IN UPLAND COTTON (Biological Sciences - PJSIR, 2002)
Because of difficulties in  producing  more  quantity and  cheaper F1  hybrid  seed, recently  a possible  alternative  of using  F2 1 hybrid  seed  is receiving  more  importance . Fou rteen F and F hybrids  and  their  parents  were  compared  for  number of 2 bolls, seed cotton yield, li nt %, fibre length and fi bre uniformity ratio. F1 hybrids were superior to F2 hybrids and  their  parents for all the traits. However, some of F2 hybrids were also  better  than  their  high  parents.  The percent  increase  of some F2  hybrids against their  high parent was 66.7% in n um ber of bolls  per  plant, 45.6% in     seed cotton yield , 8.1 in  lint%, 4.4% in fibre length and 4.8% in uniformity ratio. As expected, F2 hybrids have generally expressed about 50% of inbreeding  depression; nevertheless,  deviations  to this expectation  were  also noted  in  particular  characters and crosscombinations.  These deviations  were probably  attributable to abnormal  segregation  at meiosis  due to higher  ploidy  level  of cotton plant and deterioration of dominant factors on selfing. Significant performance of some F2  hybrids  however suggested  that parental  choice and breeding  objectives  are very  important when  F, hybrids  are considered  for hybrid   cropdevelopment.